Legalitas Sunnah Dha’ifah dalam Dakwah Islamiyah - Akhmad Sagir (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Islam has two basic sources of law, namely the Qur'an and the Sunnah. The Qur'an is agreed as "al-Tsubut Qath'i" (resolution) for its narrations are acknowledged and agreed as "Qath'i al-Wurud". While the second source (the Sunnah), not all its narrations are believed to be "authentic". Therefore when an al-Sunnah has undoubted "authentic" qualty, then no one can dismiss its legality. In the case of a weak hadith (al-Sunnah al-dha'ifah) majority of scholars do not allow it to be used as an argument for the faith and the law, but some scholars allow it to be used as an argument, especially for fahda‟il al-A'mal (virtuous acts). Fadha'il al-A'mal are more relevant with dakwah framework that requires wisdom and exemplary conduct.